Extracurricular Management In Improving Student Non-Academic Achievement - Muhammad Zaironi (Jurnal Serambi Ilmu, 2024)
This study aims to determine how the management of extracurricular activities in improving students’ non-academic achievement at MAN 1 Malang and MA Al-Khoirot Malang, with sub-focuses including: (1) planning extracurricular activities, (2) implementing extracurricular activities, (3) evaluating activities extracurricular, (4) non-academic achievements produced. This study uses a qualitative approach by designing a multi-site study. The data collection is done by interview, observation and documentation. Sources of research data include school principals, vice principals, and coordinator of extracurricular activities. The results showed that: The management of extracurricular activities at MAN 1 and MA Al-Khoirot Malang has been carried out well. This can be seen from the indicators of the management of extracurricular activities carried out and from the results, the existence of extracurricular activity planning, implementation and evaluation, as well as the achievements he achieved in one year showed an increase. This is due to the well-planned and well-implemented management of extracurricular activities, as well as the gradual evaluation according to the program so that students experience an increase in their non-academic achievement.